Assessment of Farmers Adaptability of a Pedal Pump - Iqbal, MT (Journal of Agriculture & Rural Development, 2010)
Manual pumps are now a days very popular among small and marginal farmers of Bangladesh. Among the manual pumps the farmers predominantly use treadle pumps. It was found from study that the present structural design, the operation of the pump is tedious and at the same time very ineffective, which needs necessary modifications. An improved version of treadle pump called pedal pump was designed and fabricated at Agricultural Engineering Division, Bangladesh Sugarcane Research Institute (BSRI), Ishurdi, Pabna, which is by-cycle operated, comfortable to operate, capable of lifting surface and ground water having discharge range from 60-100 litres per minute at different suction heads (up to 7 meters). The objective of the study was to assess the socio-economic profile of the pedal pump users and to determine the adaptability of the pedal pump by the farmers as perceived by them. For demonstration of pedal pump 12 demonstrated and 120 non-demonstrated farmers were selected at Pabna, Thakurgaon and Chuadanga district of Bangladesh. Demonstration farmers have smaller land holding (0.47 ha) and higher number of family size (8 Nos.) compared to non-demonstration farmers. Pedal pump has a potentiality to use as a small-scale irrigation device opined by 92% demonstration and 88% non-demonstration farmers. Sixty seven percent demonstrated and 80% of non-demonstrated farmers expressed that the price of pedal pump were satisfactory and 67% demonstrated and 64% non-demonstrated farmers expressed their willingness to buy pedal pump. Operation of the pedal pump, as perceived by the farmers is much easier and comfortable than treadle pump. Key words: Marginal farmers; assessment; farmer's adaptability; pedal pump. DOI: 10.3329/jard.v7i1.4435 J Agric Rural Dev 7(1&2), 145-150, June 2009